Manajemen Krisis Public Relation dalam Menanggapi Kekerasan Sosial dan Meningkatkan Harmoni dengan Masyarakat : Studi Kasus pada Pondok Pesantren As-Sunah Lombok - Nuraenun, Nuraenun (STAI Darul Kamal NW Kembang Kerang, 2024)
The occurrence of acts of vandalism and anarchy at Assunah Islamic Boarding School in Lombok resulted in damage to several facilities within the boarding school, and several vehicles parked at the location were also targeted for arson. The purpose of this research is to explore the crisis management strategies implemented by Assunah Islamic Boarding School in Lombok using the Image Restoration theory by William L Benoit. The research approach applied is constructivism with a qualitative method and a particularistic case study, focusing on the events, situations, phenomena, and specific programs at Assunah Islamic Boarding School in Lombok in response to acts of violence and public demonstrations following the spread of video clips discrediting some ancestral graves in Lombok and the rapid growth of the boarding school after the incident. Research data were collected through in-depth interviews with key informants within Assunah Islamic Boarding School in Nyaka, East Lombok, and other reliable informants. The research findings indicate that the Public Relations efforts of Assunah Islamic Boarding School in Lombok successfully convinced the public through persuasive means, and the responsibility for the anarchic actions was entirely handed over to the authorities.